Study of Serum Electrolytes in Acute Renal Failure; Pre and Post Dialysis - S. B, Gaikwad; A. B., Agte; G. S., Niturkar (International Journal of Innovative Research in Medical Science, 2018)
Measurement of the concentration of electrolytes in serum levels of sodium, potassium, calcium, magnesium and chloride is important in acute renal failure (ARF). The level of these electrolytes in serum was analyzed in predialysis and post dialysis. The data obtained revealed that decrease in serum level of sodium, potassium, magnesium and chloride while increase in serum level of calcium was seen in post dialysis as compared to predialysis.